2009
DOI: 10.4049/jimmunol.0901070
|View full text |Cite
|
Sign up to set email alerts
|

MS4A4B Is a GITR-Associated Membrane Adapter, Expressed by Regulatory T Cells, Which Modulates T Cell Activation

Abstract: In the aftermath of thymic negative selection, natural and adaptive regulatory T cells (Tregs) must acknowledge peripheral, “danger-free” self-Ag to ensure their sustained activity. In this paper, we show that natural and adaptive Tregs or T cells transduced with cDNA for Foxp3, just like Th1 cells, express members of the MS4A family of transmembrane molecules. Naive T cells transduced with MS4A4B become able to respond to lower levels of Ag. Using two family members, MS4A4B and MS4A6B, as baits in a yeast spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 38 publications
6
47
0
Order By: Relevance
“…The functions of other members remain largely unclear. Since we cloned MS4a4B from the thymus of C57BL/6 mice, data from our studies and others have shown that MS4a4B is highly expressed in T cells and is closely related to the regulation of CD4 + T cell-mediated immune responses [1], [19], [20], suggesting its importance in adaptive immunity.…”
Section: Introductionmentioning
confidence: 75%
“…The functions of other members remain largely unclear. Since we cloned MS4a4B from the thymus of C57BL/6 mice, data from our studies and others have shown that MS4a4B is highly expressed in T cells and is closely related to the regulation of CD4 + T cell-mediated immune responses [1], [19], [20], suggesting its importance in adaptive immunity.…”
Section: Introductionmentioning
confidence: 75%
“…It has been shown recently that other MS4A family members are capable of transmitting cellular signals by binding to regulatory proteins; for example, MS4A4B is able to cluster with the GC-inducible costimulatory molecule GITR in supramolecular complexes in the plasma membrane in cis lowering the threshold for GITR activation in regulatory T-cells. 38 Similarly, MS4A8A could cluster with as yet unidentified surface receptors in cis to alter their activation threshold or signaling behavior, especially in GC-treated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Th1 and Th17 cells also increased microglial production of inflammatory cytokines [52]. To date, lots of researchers have confirmed that the MS4A family gene overexpression can increase activation of T cells [39,54]. MS4A4B as a member of the MS4A family gene had been found to regulate apoptosis and survival of activated T cells [39][40][41].…”
Section: Potential Roles For Ms4a Cluster In Admentioning
confidence: 99%